2012
DOI: 10.3396/ijic.v8i1.009.12
|View full text |Cite
|
Sign up to set email alerts
|

Contaminated air conditioners as potential source for contaminating operation theater environment

Abstract: Five patients developed endophthalmitis after cataract surgery. on evaluation of operation-theatre complex, fungal spores were demonstrable from environment and surfaces. Air conditioner's filters were grossly contaminated. Aspergillus and Mucor spp. were isolated. Phenotypically similar fungi were isolated from three of the patients (Aspergillus spp. from two and Mucor spp. from one). As a follow up study, filters of the air conditioning devices in twenty five operating rooms of hospitals nearby were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…However, fungus in air conditioners in tutorial rooms of Faculty of Medicine shows a higher prevalence of Aspergillus and Mucor. 11 Nonetheless, there are no Standards or Threshold Limit Values (TLVs) established yet to judge what the acceptable, tolerable, or normal quantity of mold. 13,14 In conclusion, it is revealed that the pathogenic fungi are presence in the air conditioners from tutorial rooms with the frequency of 94.1%.…”
Section: Discussionmentioning
confidence: 99%
“…However, fungus in air conditioners in tutorial rooms of Faculty of Medicine shows a higher prevalence of Aspergillus and Mucor. 11 Nonetheless, there are no Standards or Threshold Limit Values (TLVs) established yet to judge what the acceptable, tolerable, or normal quantity of mold. 13,14 In conclusion, it is revealed that the pathogenic fungi are presence in the air conditioners from tutorial rooms with the frequency of 94.1%.…”
Section: Discussionmentioning
confidence: 99%
“…The Samples were collected in four seasons of the year. About 38 samples each season from indoor air and 11 samples from air conditioners collected by using Settle Plate Method (Passive Air Sampling) on blood agar for bacteria culture (Genet et al, 2011;Kelkar and Kulkarni, 2011) and Sabouraud's Dextrose Agar (SDA) plate plus 50µg/ml of gentamicin for fungi culture (Kelkar and Kulkarni, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Each plate was leaving open to the air for a 30 minutes (Kelkar and Kulkarni, 2011), a meter to 1.5m above the floor and a meter from the wall (Ekhaise and Ogboghodo, 2011). The air samples collected (at 9-11 AM) within a given day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other opportunistic fungi isolated in this study are also known to cause nosocomial infections. 6,7,27 The spores of Aspergillus have a diameter of 1.5-3.5 µm and a settling velocity of approximately 1m/hour in still air. With this buoyancy, the spores which resist drying can remain in the air indefinitely 7 and get settled into surgical wounds as well as inhaled.…”
Section: Discussionmentioning
confidence: 99%